1999
DOI: 10.1152/ajpgi.1999.276.3.g711
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duodenal distension on antropyloroduodenal pressures and perception are modified by hyperglycemia

Abstract: Marked hyperglycemia (blood glucose ∼15 mmol/l) affects gastrointestinal motor function and modulates the perception of gastrointestinal sensations. The aims of this study were to evaluate the effects of mild hyperglycemia on the perception of, and motor responses to, duodenal distension. Paired studies were done in nine healthy volunteers, during euglycemia (∼4 mmol/l) and mild hyperglycemia (∼10 mmol/l), in randomized order, using a crossover design. Antropyloroduodenal pressures were recorded with a manomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 40 publications
4
36
1
1
Order By: Relevance
“…Acute hyperglycaemia has been shown to induce relaxation of the proximal stomach, suppression of the frequency and propagation of antral pressure waves, and an increase in pyloric tone. Moreover, marked hyperglycaemia can also produce tachygastria and un-coordinated motor activity of different parts of the stomach [8,9]. Studies have also shown that acute hyperglycaemia slows gastric emptying of both solid and liquid nutrients in patients with established autonomic neuropathy and can also attenuate the prokinetic effect of intravenous erythromycin on gastric emptying [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…Acute hyperglycaemia has been shown to induce relaxation of the proximal stomach, suppression of the frequency and propagation of antral pressure waves, and an increase in pyloric tone. Moreover, marked hyperglycaemia can also produce tachygastria and un-coordinated motor activity of different parts of the stomach [8,9]. Studies have also shown that acute hyperglycaemia slows gastric emptying of both solid and liquid nutrients in patients with established autonomic neuropathy and can also attenuate the prokinetic effect of intravenous erythromycin on gastric emptying [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the excitability of glucoresponsive neurons is determined by the extracellular glucose concentration. This may explain why acute changes in the blood glucose concentration have a substantial effect on gastrointestinal motor reflexes (MacGregor et al, 1976) and visceral sensation (Lingenfelser et al, 1999). Although it has been assumed that the gastrointestinal motor symptoms and alterations in gut sensations observed in patients with diabetes mellitus were part of a generalized autonomic neuropathy, they may actually be produced by changes in the activity of enteric neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that marked hyperglycemia, which is characteristic of diabetes, decreases the motility index and propagation of duodenal and jejunal waves [5], reduces the cycle length of interdigestive motor activity in the fasted state [6], and slows small-intestinal transit [7,8]. Elevation of the blood glucose to the upper end of the physiological range decreases duodenal compliance while increasing the stimulation of duodenal waves [9].…”
Section: Introductionmentioning
confidence: 99%